Global perspective on the burden of smoking-attributable low back pain: new insights from the global burden of disease study 2021 - Chen, Yufan; Sun, Wenjia; Lian, Xionghan; Wang, Zhiqiang (Frontiers in Musculoskeletal Disorders, 2025)
BackgroundThis study aimed to examine the evolving trends in the global burden of smoking-attributable low back pain (LBP) from 1990 to 2021 and predicted disease burden until 2035.MethodsUsing Global Burden of Disease (GBD) 2021 data, we analyzed years lived with disability (YLDs) from smoking-attributable LBP across 204 countries. We assessed trends by sex, age, and region using estimated annual percentage change (EAPC) and projected future burden via Bayesian age-period-cohort (BAPC) modeling.ResultsIn 2021, smoking-attributable LBP caused 8.82 million (95% UI 5.18–13.13) YLDs globally, with an age-standardized YLD rate (ASYR) of 102.0 per 100,000 (EAPC = −1.26, 95% CI −1.28 to −1.24). The burden showed marked geographic variation, being highest in Eastern Europe (ASYR: 194.0, 95% UI 115.5–290.1) and lowest in Western Sub-Saharan Africa (ASYR: 32.7, 95% UI 18.3–50.7). And high SDI regions recorded the highest ASYR (173.8, 95% UI 101.7–261.1), 3.2-fold higher than low SDI regions (54.6, 95% UI 31.3–83.6) in 2021. Middle SDI regions demonstrated the most significant ASYR reduction (percentage change in ASYR: −33.8%, 95% UI −36.3 to −31.7) from 1990 to 2021. Males consistently bore 62.7% of the burden, with peak incidence occurring at ages 60–64 (ASYR: 294.2, 95% UI 162.0–480.3). Projections indicate the ASYR will decline to 82.7/100,000 by 2035, representing a 45.9% reduction from 1990 levels.ConclusionWhile global ASYR trends show improvement, persistent disparities by sex, age, and region underscore the need for targeted interventions. Priority should be given to: (1) male-focused smoking cessation programs, (2) workplace interventions for middle-aged populations, and (3) enhanced tobacco control policies in high-burden regions.